THE ROLE OF THE LEGAL DOCUMENTATION AND INFORMATION NETWORK (JDIH) IN THE FORMULATION AND DETERMINATION OF PUBLIC POLICIES (Analysis of the Legal Bureau of the Regional Secretariat of Central Java Province) - Wardani, Lilis; Hafidz, Jawade (Jurnal Hukum Khaira Ummah, 2023)
This study aims to determine how the role of JDIH in the formulation and determination of public policy, how the weaknesses encountered, in the formulation and solution network documentation and law information and public policy decisions.This research uses data collection method with literature study, research conducted later to be done to obtain data that is through study to legislation, consist of primary law material, secondary law material and tertiary material, and writings of practitioners and documents of relevance With research. The specification of this research is descriptive analytical research that is by analyzing and describing how the role of network documentation and law information, how weaknesses and solutions.Existence of JDIH Province of Central Java has a very important role because it is needed in every public policy formulation activities ranging from planning, design, and post-policy formulation. However, in every public service activities there are always weaknesses that are faced. Weaknesses faced are human resources, regulation, facilities and infrastructure, and budget. For that legal firm SETDA Central Java trying to find a solution to the weakness faced that is equipKeywords: Documentation And Legal Information Networks (JDIH), Public Policy